THE EFFECTIVENESS OF USING STORY PYRAMID STRATEGY TO THE READING COMPREHENSION ADVANCEMENT - Tsuraya, Annisa Shofa; Rahman, Indah Fadhilah; Ulfa Lis Adhayanti (Univeristas Islam Negeri (UIN) Alauddin Makassar, 2023)
The objective of this research was to find out the level effectiveness of using Story Pyramid Strategy to the reading comprehension advancement. The quasi-experimental method research design is used to carry out this research. There are experimental and control class. The experimental class consists of 20 students and the controlled class consists of 20 students. The Story Pyramid Strategy was applied in the experimental class as a treatment to train students in reading narrative text. The instrument used in this research is a test in multiple choices. The researchers used a pre-test as an instrument before conducting the treatment of Story Pyramid Strategy and a post-test as an instrument after conducting the treatment of Story Pyramid Strategy. The result of this research after conducting the treatment of Story Pyramid Strategy in the experimental class shows there was an advancement in students’ reading comprehension in reading narrative text. The Story Pyramid Strategy enables the students summarize the most important parts of text and got the detail and specific information. Story Pyramid also made students more active and creative in learning process. The researcher found that the use of story pyramid strategy to help the students understand the text and got the detail and specific information especially in narrative text.